Long-Term Clinical Outcomes in Treatment-Naïve Patients With Orbital Adnexal Mucosa-Associated Lymphoid Tissue Lymphoma: A Single-Center Study - Min, Gi-June; Kim, Sung Eun; Kim, Tong Yoon; Jeon, Young-Woo; O, Joo Hyun; Choi, Byung-Ock; Park, Gyeongsin; Yang, Suk-Woo; Cho, Seok-Goo (Frontiers in Oncology, 2022)
Ocular adnexal mucosa-associated lymphoid tissue (MALT) lymphoma (OAML) is the most common type of ocular lymphoma with a higher prevalence in Asia than in Western countries. OAML represents 1%–2% of all non-Hodgkin's lymphoma, 5%–15% of extranodal lymphomas, and approximately 55% of orbital malignancies. “Watch and wait” after biopsy or surgical resection, radiation therapy, and systemic treatment, including antibiotics administration and chemotherapy with various combinations of regimens can be considered for OAML treatment. Radiotherapy is adapted for limited-stage disease with excellent clinical outcomes of 85–100% complete remission and relatively superior local control efficacy and treatment duration. In contrast, chemotherapy has rarely been tested as frontline therapy. Nonetheless, several studies have reported a favorable response and long duration of progression-free survival using chemotherapy adaptations. When the disease involves both eyes or spreads beyond the conjunctiva, the risk of recurrence increases and limited-stage OAML has a recurrence rate of approximately 25% following radiotherapy only. Therefore, although recent consensus in the literature is that patients with limited-stage OAML recommended treating with radiation, physicians may choose the treatment modality not only by its efficiency but also by its adverse events profile and patients' well-being. Herein, we present a large single-center study on OAML that included 292 patients who were followed up for up to 237 months. We collected and analyzed real-world data focusing on treatment outcomes and the role of radiotherapy as frontline therapy, and aimed to compare outcomes and complication profiles of chemotherapy, especially in limited-stage OAML, to identify an optimal treatment strategy.